1989
DOI: 10.3109/02713688908995191
|View full text |Cite
|
Sign up to set email alerts
|

Association of HLA-DR4 with ocular cicatricial pemphigoid

Abstract: HLA typing for A, B, and C locus antigens was performed on 70 patients with ocular cicatricial pemphigoid (OCP) and on 1849 controls. Additionally, typing for DR and DQ antigens and for the complement proteins (C2, factor B, C4A, and C4B) was performed on 63 patients and on the same control population. A significantly higher incidence of the following antigens was found in the OCP patients when compared to the control population: DR4 (43% in patients compared to 18% in controls, p = 0.0001); DR5 (41% compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0
1

Year Published

1991
1991
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(10 citation statements)
references
References 22 publications
0
9
0
1
Order By: Relevance
“…The antibody in pemphigus vulgaris is directed against a protein of the epidermal intercellular cement substance (31), whereas the antigen(s) of OCP have not been definitively characterized (32). Although both diseases are associated with HLA-DR4 (11,33) in some patients, in other respects the MHC associations are, quite different. In this report, we have shown that the HLA-DR4 increase in OCP appears to be secondary to the increase in DQw7 and not to a DR4-carrying extended haplotype.…”
Section: Methodsmentioning
confidence: 99%
“…The antibody in pemphigus vulgaris is directed against a protein of the epidermal intercellular cement substance (31), whereas the antigen(s) of OCP have not been definitively characterized (32). Although both diseases are associated with HLA-DR4 (11,33) in some patients, in other respects the MHC associations are, quite different. In this report, we have shown that the HLA-DR4 increase in OCP appears to be secondary to the increase in DQw7 and not to a DR4-carrying extended haplotype.…”
Section: Methodsmentioning
confidence: 99%
“…Initially, HLA-B12 was reported to be associated with OCP [13]. This association was not confirmed by a later study [15], and HLA-DR4. -DR5.…”
mentioning
confidence: 86%
“…-DR5. -DQw3, -B8, -B35 and -B49 were reported to be associated with OCP [15]. Subsequently, restriction fragment length polymorphism analyses sub typed DQw3 to be the DQw7 (DQB 1*0301) allele [ 16], Ail the previous studies, however, appeared to include a clini cally and immunopathologically heterogeneous group of patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…O HLA de classe I não parece estar associado à doença (1) , embora Mondino et al (40)(41)(42) tenham sugerido associação com o antígeno HLA-B12. Em 1989, foi sugerida a associação com os antígenos HLA-A2, -B8, -B35 e -B49 (43) .…”
Section: Penfigóide Cicatricial Ocularunclassified